The impact of electric vehicles on the power market. Issue 4 (22nd April 2015) - Albanese, Lorenzo; Ciriminna, Rosaria; Meneguzzo, Francesco; Pagliaro, Mario
Abstract We investigate the impact of massive electric vehicle (EV) adoption onto the power market, both in the presence and in the absence of significant photovoltaic (PV) generation. Although results are derived taking into consideration Italy's power market, results are of relevance also to other industrialized countries. One of the most important outcomes of the analysis, that is, the synergistic and beneficial effect on the overall energy bill of the concomitant expansion of EVs utilization and the growth of the renewable energy generation, particularly solar photovoltaics. The Conclusions provide arguments for policymakers for further support to sustainable mobility in their regions.